Ta’dib (Penanaman Adab) di Pesantren - Munzillah, Indiarti Muafiqoh; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
Education is an activity carried out to develop the abilities of students and the cultivation of civilization for students. Pesantren is one of the educational institutions that is the choice of parents with the rampant cases of crisis outside, pesantren are educational institutions where students in the learning process do not commute but live in Islamic boarding schools. Pesantren will provide facilities in the form of dormitories and other needs, in Pesantren learn religious knowledge, memorize the Qur'an, and instill adab to students (santri). The research method carried out is using qualitative research methods with a literature model. The stages in analyzing data are doing it by reducing data, presenting data, and drawing conclusions. Researchers reduce the educational literature and then present it systematically. The final stage is to draw conclusions from critical analysis. There are very important things to be instilled in students, but in fact not only students but all humans. Because with good civility, it reflects good morals as well. The purpose of the study is to find out the meaning of ta'dib (adab planting) and to find out the process of ta'dib (adab planting) in Islamic boarding schools. Ta'dib is to instill and implement adab through the educational order, the implementation of which requires discipline, as well as punishment that leads to warnings that make humans have civilization in studying or in social life. The process of ta'dib actually starts from the family, while from pesantren several methods are carried out, namely 1) the hiwar method, 2) the uswah method, 3) the riyadhah method, 4) the qishah (story) method, 5) the ibrah or mau'idzah method, 6) the targhib and tarhib methods, 7) the proverbs method. Adab planting in Islamic boarding schools cannot be done instantly or quickly, but requires a long time process. Actually, planting adab is done early in the family environment. Planting adab is carried out by several methods. And its implementation is not only for students but for the entire pesantren community.